A new approach for dissimilar aluminum-steel impact spot welding using vaporizing foil actuators. (October 2020) - Kapil, Angshuman; Mao, Yu; Vivek, Anupam; Cooper, Ronald; Hetrick, Elizabeth; Daehn, Glenn
Abstract: Dissimilar joining of aluminum to steel is an important industrial and academic problem. The present study reports the application of a novel approach in impact welding where a pocket machined on the flyer sheet generates the requisite standoff, enabling joining of commonly used automotive aluminum alloys to high-strength low-alloy (HSLA) steels. The new approach enables impact spot welding of heat treatable AA6111-T4 aluminum (Al) alloy to bare, hot-dip galvanized and e-coated HSLA 340 steel (with local removal of the coating on the faying surface) as well as of high-pressure vacuum die cast Aural 2 Al alloy to hot-dip galvanized HSLA 340 steel. Characterization of the welded samples via lap-shear and coach peel testing demonstrated high joint strengths with button pullout failure modes in all weld pairs. Optical microscopy of the weld cross-sections revealed defect-free joints displaying typical impact welded interface morphology. A significant outcome of the novel impact spot welding approach was the ability to produce joints exhibiting flat external target surfaces with unperturbed coating, a potential enabler for mixed metal joining applications involving pre-treated, e-coated, or painted materials.